Nostalgia for the Present Ethnography and Photography in a Moroccan Berber Village - Deseyn, Bart (Debates on Islam and Society, 2014)
Anthropology and photography have been linked since the nineteenth century, but their relationship has never been entirely comfortable-and has grown less so in recent years. Nostalgia for the Present aims to repair that relationship by involving intentional participants in an inclusive conversation; it is the fruit of a collaboration among an ethnographer, a photographer, a group of Moroccan farmers, and Abdelkrim Bamouh-a native intellectual whose deep understanding of rural Morocco made him not merely a translator but a facilitator of the dialogue. The result is an arresting portrait of everyday life in Tagharghist, a contemporary High Atlas village. The pictures are central, and the text bilt around them creates a dialogical form of visual ethnography. Nostalgia for the Present is both a memorialization of a people and a way of life, and a rich foray into the potential of interdisciplinary collaboration. The photos in this book evoke a sense of nostalgia, a longing, and the words explore the contexts and ambiguities that vitalize it. As the book concludes, nostalgia happens in our present, and is about our future. It is a call from our heart (or our liver, as villagers would say) to attend carefully to something we are leaving, something our gut tells us we ought to cherish and preserve, and bring with us on our inexorable march into the unknown.